2006
DOI: 10.1183/09031936.06.00006106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multiplex PCR for bacterial pathogens applied to bronchoalveolar lavage

Abstract: The present study assessed the diagnostic usefulness of a multiplex PCR (mPCR) for Streptococcus pneumoniae, Haemophilus influenzae, Mycoplasma pneumoniae and Chlamydophila pneumoniae applied to bronchoalveolar lavage (BAL).Fibreoptic bronchoscopy was performed on 156 hospitalised adult patients with lower respiratory tract infection (LRTI) and 36 controls. BAL fluid was analysed with bacterial culture and mPCR.By conventional diagnostic methods, S. pneumoniae, H. influenzae, M. pneumoniae and C. pneumoniae we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 38 publications
4
38
0
1
Order By: Relevance
“…This high detection rate through PCR is similar to the study in which respiratory microorganisms were detected in 97% of the children with CAP by Honkinen et al [12]. Strålin et al suggested that bronchoalveolar lavage multiplex PCR for S. pneumonia, M. pneumoniae and C. pneumoniae appears to be a useful etiological tool in lower respiratory tract infection patients and this method may be a valuable supplement to bronchoalveolar lavage culture [11]. Another probable reason for high etiologic agent recovery may be the severity of disease and the poor immune response in the elder patients requiring hospitalization.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This high detection rate through PCR is similar to the study in which respiratory microorganisms were detected in 97% of the children with CAP by Honkinen et al [12]. Strålin et al suggested that bronchoalveolar lavage multiplex PCR for S. pneumonia, M. pneumoniae and C. pneumoniae appears to be a useful etiological tool in lower respiratory tract infection patients and this method may be a valuable supplement to bronchoalveolar lavage culture [11]. Another probable reason for high etiologic agent recovery may be the severity of disease and the poor immune response in the elder patients requiring hospitalization.…”
Section: Discussionsupporting
confidence: 69%
“…This is probably due to i) molecular tests which provided doubled increase in identification rate [6,11] ii) respiratory samples obtained by protected deep tracheal aspiration. This high detection rate through PCR is similar to the study in which respiratory microorganisms were detected in 97% of the children with CAP by Honkinen et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study specimens showed virtually no carriage of the other nine bacterial and viral pathogens. The findings of this work, combined with those in previous reports showing good sensitivities and specificities for symptomatic patients (11,20,24,25,29,40), suggest that molecular assays testing for these nine pathogens in respiratory secretions will have good utility in clinical practice. The low rate of detection of NA in serum is reassuring in the presence of comparably high rates of detection in specimens from the nasopharynx and skin, sites that have been implicated previously as potentially contributing to the detection of pathogens in serum.…”
Section: Discussionmentioning
confidence: 59%
“…Over the past decade, several studies aimed to define parameters that allow the distinction between bacterial and viral infections causing LRTI. The methods used included polymerase chain reaction (PCR), procalcitonin determination and other clinical information [8,9,10,11,12,13,14,15]. However, the information obtained by medical history, physical examination, routine laboratory parameters and chest radiography is not sufficient for a clear differential diagnosis of the cause of LRTI.…”
Section: Introductionmentioning
confidence: 99%